Design and development of a portable satellite tracking ground station. Part 1 : antenna and tracking mechanism - Muhammad Fariq Mohd Isa (Nanyang Technological University, 2020)
There are thousands of satellites orbitting our planet and some or these are made by the personnel of Nanyang Technological University (NTU). These satellites serve their individual purposes from weather imagery to communications. These data are transmitted wireless through space between the satellite and ground station. Ground stations are vital instruments to decode these data, and to transmit new information to these satellites. Similar to the satellites, ground station vary from very large system to small portable devices. These portable devices are made possible by the integration of motors, micro-controller and antenna. Thus, this project aims to create a portable ground station with a rotator built with set of components that are cheaper compared to the commercially available rotators such as the YAESU in the market. This standalone device then can be used for research purposes.